Faktor-Faktor Yang Berhubungan Dengan Kejadian Robekan Perineum Pada Persalinan Normal di PMB Roslina Kabupaten Ogan Komering Ulu Tahun 2023 - Heriani Heriani; Indra Sulistiawati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Perineal robekane is a birth canal wound that can occur spontaneously due to a stiff perineum, precipitate labor, wrong delivery leadership, lack of good cooperation with the mother during the birth process, improper use of manual maneuvers. Perineal robekane due to episiotomy expands the birth canal due to large, premature babies, abnormalities in location and delivery with vacuum forceps. This study aims to determine the factors that influence the incidence of perineal robekane in normal delivery at PMB Roslina,S.Keb in 2023 with a population of all women giving birth normally with a total of 80 mothers. The research method used a cross sectional and sampling technique, data analysis using square test. In this study, it was found that there was a relationship between the age of the mother and the incidence of perineal robekane in normal delivery, a significance p-value = 0.000 (a <0.05), while the relationship between parity and the incidence of perineal robekane had a significance p-value = 0.000 (a <0.05) and the relationship between BBL and the incidence of perineal robekane, p-value = 0.000 (a <0.05). So there is a relationship between age, parity and BBL with the incidence of perineal robekane. There is a significant relationship between the appropriate age factor, and BBL and the incidence of perineal robekane in normal delivery.